KONSEP PERPAJAKAN DALAM KITAB AL-KHARAJ RELEVANSI DI INDONESIA - Hasni, Hasni; Maysarah, St (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
During the time when Harun Ar-Rashid was appointed became Qadhi al-Qudhah (Chief Justice of the Supreme Court), at that time the people's welfare increased to trade, the economy in the city of Baghdad was progressing, he made the book of Al-Kharaj as a guide in terms of taxation, economics and others, furthermore regarding the Relevance of Al- kharaj in Indonesia which can be seen from Customs which has been regulated in Law no. 39 2007, where it is explained that customs are state levies imposed on certain goods that have the characteristics or characteristics regulated in the law, while in al-kharaj the adat work of abu yusuf is called Usyur. Where Usyur is a tax collected on merchandise that enters an Islamic state, hereinafter in Indonesia the land and building tax is called (PBB) Building Tax, where in the al-kharaj book, Abu Yusuf argues that the land tax rate must be determined by the method for results (muqasamah), Furthermore, it can be seen from the tax collection system in Indonesia using a tax collection system which is the principle of the Self AssessmentSystem, where people are required to pay taxes and the public is required to understand the law of implementing taxes, while in the book Al-Kharaj Abu Yusuf is to use the Qabalah system.